Association between impaired glucose tolerance and circulating concentration of Lp(a) lipoprotein in relation to coronary heart disease. Issue 6908 (2nd October 1993) - Farrer, M; Game, F L; Albers, C J; Neil, H A; Winocour, P H; Laker, M F; Adams, P C; Alberti, K G
Abstract : OBJECTIVE–To examine whether impaired glucose tolerance and raised Lp(a) lipoprotein concentrations are associated in subjects with coronary artery disease. DESIGN–Study of two subject populations, one with and one without symptomatic coronary artery disease. Case-control analysis of patients with impaired glucose tolerance and normal glucose tolerance performed in each subject population independently. SETTING–A general practice and a hospital ward in Newcastle upon Tyne. SUBJECTS–517 apparently healthy subjects, 13 with impaired glucose tolerance, and 245 patients who had undergone coronary artery bypass graft surgery 12 months before, 51 with impaired glucose tolerance. MAIN OUTCOME MEASURES–Serum Lp(a) lipoprotein concentration, plasma glucose concentration before and after oral challenge with 75 g glucose monohydrate, and Lp(a) lipoprotein isoforms. RESULTS–In both the asymptomatic subjects and the subjects with coronary artery disease there was no significant difference between subjects with impaired glucose tolerance and subjects with normal and body mass index in serum Lp(a) lipoprotein concentrations (geometric mean 61 (geometric SD 4) mg/l v 83 (5) mg/l for asymptomatic subjects, 175 (3) v 197 (2) for subjects with heart disease), nor was there any difference in the proportion of subjects who had Lp(a) lipoprotein concentrations > 300 mg/l (31% v 23% for asymptomatic subjects, 37% v 37% for subjects with heart disease). For both subject groups there was no significant correlation between Lp(a) lipoprotein concentration and plasma glucose concentration after a glucose tolerance test, nor did Lp(a) lipoprotein concentration vary by quintile of glucose concentration after the test. Examination of Lp(a) lipoprotein isoforms in the subjects with coronary artery disease revealed an inverse relation between isoform size and plasma Lp(a) lipoprotein concentration, but there was no evidence that impaired glucose tolerance was associated with particular Lp(a) lipoprotein isoforms. CONCLUSION–Raised Lp(a) lipoprotein concentrations are not responsible for the association between impaired glucose tolerance and coronary artery disease.